Is Arc mRNA Unique: A Search for mRNAs That Localize to the Distal Dendrites of Dentate Gyrus Granule Cells Following Neural Activity - de Solis, Christopher A.; Morales, Anna A.; Hosek, Matthew P.; Partin, Alex C.; Ploski, Jonathan E. (Frontiers in Molecular Neuroscience, 2017)
There have been several attempts to identify which RNAs are localized to dendrites; however, no study has determined which RNAs localize to the dendrites following the induction of synaptic activity. We sought to identify all RNA transcripts that localize to the distal dendrites of dentate gyrus granule cells following unilateral high frequency stimulation of the perforant pathway (pp-HFS) using Sprague Dawley rats. We then utilized laser microdissection (LMD) to very accurately dissect out the distal 2/3rds of the molecular layer (ML), which contains these dendrites, without contamination from the granule cell layer (GCL), 2 and 4 hrs post pp-HFS. Next, we purified and amplified RNA from the ML and performed an unbiased screen for 27,000 RNA transcripts using Affymetrix microarrays. We determined that Activity Regulated Cytoskeletal Protein (Arc/Arg3.1) mRNA, exhibited the greatest fold increase in the ML at both timepoints (2 hr and 4 hr). In total, we identified 31 transcripts that increased their levels within the ML following pp-HFS across the two timepoints. Of particular interest is that one of these identified transcripts was an unprocessed micro-RNA (pri-miR132). Fluorescent in situ hybridization (FISH) and qRT-PCR were used to confirm some of these candidate transcripts. Our data indicates Arc is a unique activity dependent gene, due to the magnitude that its activity dependent transcript localizes to the dendrites. Our study determined other activity dependent transcripts likely localize to the dendrites following neural activity, but do so with lower efficiency compared to Arc.